A gerência recente do endividamento público brasileiro - Pedro Maia; Márcio G. P. Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2011)
– We use two frameworks to analyze the recent Brazilian public debt management. The first one encompasses the Brazilian optimal public debt management analysis through the examination of the correlations among the main variables to which the public debt is indexed. The second seeks to address the consequences of recent Brazilian economic policies, such as international reserves accumulation through sterilized interventions by the Central Bank and excessive capitalization of federal financial institutions. Those policies have important, albeit often ignored, fiscal impacts, which became important to determine the current size, maturity and composition of the public debt stock.
Keywords: H63; E58; 330; optimal public debt management; Brazil; public bonded debt. Jel Codes: H63; E58; Schuldenmanagement; Öffentliche Schulden; Wirtschaftspolitik; Brasilien